Global survey of medicinal plants during lactation and postpartum recovery: Evolutionary perspectives and contemporary health implications. (24th April 2021) - Sibeko, Lindiwe; Johns, Timothy
Abstract: Ethnopharmacological relevance: Cross-cultural comparison of plants used during lactation and the postpartum period offers insight into a largely overlooked area of ethnopharmacological research. Potential roles of phytochemicals in emerging models of interaction among immunity, inflammation, microbiome and nervous system effects on perinatal development have relevance for the life-long health of individuals and of populations in both traditional and contemporary contexts. Aim of the study: Delineate and interpret patterns of traditional and contemporary global use of medicinal plants ingested by mothers during the postpartum period relative to phytochemical activity on immune development and gastrointestinal microbiome of breastfed infants, and on maternal health. Materials and methods: Published reviews and surveys on galactagogues and postpartum recovery practices plus ethnobotanical studies from around the world were used to identify and rank plants, and ascertain regional use patterns. Scientific literature for 20 most-cited plants based on frequency of publication was assessed for antimicrobial, antioxidant, anti-inflammatory, immunomodulatory, antidepressant, analgesic, galactagogic and safety properties. Results: From compilation of 4418 use reports related to 1948 species, 105 plant taxa were recorded ≥7 times, with the most frequently cited species, Foeniculum vulgare, Trigonella foenum-graecum, Pimpinella anisum, Euphorbia hirta and Asparagus racemosus, 81, 64, 42, 40 and 38 times, respectively. Species and use vary globally, illustrated by the pattern of aromatic plants of culinary importance versus latex-producing plants utilized in North Africa/Middle East and Sub-Saharan Africa with opposing predominance. For 18/20 of the plants a risk/benefit perspective supports assessment that positive immunomodulation and related potential exceed any safety concerns. Published evidence does not support a lactation-enhancing effect for nearly all the most-cited plants while antidepressant data for the majority of plants are predominately limited to animal studies. Conclusions: Within a biocultural context traditional postpartum plant use serves adaptive functions for the mother-infant dyad and contributes phytochemicals absent in most contemporary diets and patterns of ingestion, with potential impacts on allergic, inflammatory and other conditions. Polyphenolics and other phytochemicals are widely immunologically active, present in breast milk and predominately non-toxic. Systematic analysis of phytochemicals in human milk, infant lumen and plasma, and immunomodulatory studies that differentiate maternal ingestion during lactation from pregnancy, are needed. Potential herb-drug interaction and other adverse effects should remain central to obstetric advising, but unless a plant is specifically shown as harmful, considering potential contributions to health of individuals and populations, blanket advisories against postpartum herbal use during lactation appear empirically unwarranted. Graphical abstract: Image 1 Highlights: 4418 global use reports of 1948 species compiled from 331 publications. Potential role of phytochemicals in immune system and other aspects of neonatal development. Maternal benefits for involution, postpartum depression, infection, breastfeeding outcomes. Latex-producing and aromatic plants over-represented with regionally distinct patterns. Limited empirical evidence of galactogenic activity.